Relationship between Implementation of Public Health Center Management, Work Commitment and Quality of Medical Services in Public Health Centres, Karangasem, Bali - Komang Artini; I Ketut Suarjana; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Quality of health services in the public health centers in Karangasem remain a public health concern. Preliminary findings indicated there was a problem regarding implementation of health center management and working commitment of staff. This study aims to determine the association between quality of medical services, the implementation of health centre management and working commitment of staff. Methods: Study was cross-sectional among 61 doctors and nurses at 12 public health centres who were selected purposively. Data were collected from February to March 2015 using questionnaires. Data analysis using logistic regression to examine the relationship between the quality of medical services with the implementation of health center management and working commitment of staff. Results: Findings indicated that the quality of medical services, the implementation of health centre management and working commitment of staff were relatively low. The quality of medical services provided was found associated with working commitment of staff (AOR=11.3; 95%C: 1.75-73.06) and not associated with implementation of health center management (AOR=0.9; 95%CI: 0.18-5.24). Conclusion: The quality of medical services provided was found associated with working commitment of staff and not associated with implementation of health center management.